Identifikasi Keberadaan Zona Potensi Air Tanah di Perumahan GAR Menggunakan Metode Geolistrik Resistivitas - Zakia Masrurah; Rivina Annisa; Amsir; Wahidah; Nurul Azmi Harun (Program Studi Teknik Geofisika FITK UHO, 2024)
The GAR (Grand Aceh Residence) housing estate is located in Baet Village, Aceh Besar District and was constructed on the land of a pond that has been filled in and is close to the coast. The majority of residents use clean water sources from PDAM because of the difficulty of obtaining clean water. The purpose of the research was to identify potential groundwater zones and determine the conditions. The research method used was electrical resistivity method, SuperSting R8/IP with Wenner-Schlumberger configuration. The research was conducted in 3 lines with 6 m spacing. RES2DINV software based on the least square inversion approach was used for data processing. The results obtained show resistivity values varying from 0.1 - 100 Ohm.m with a depth penetration of up to 28.8m. There are 3 lithological layers obtained, namely clay (0.1 - 1.5 Ohm.m), clayey sand (1.5 - 17.7 Ohm.m), and sand (17.7 - 100 Ohm.m). The groundwater presence zone is assumed to be in the sand layer. There are 2 types of groundwater obtained, which are shallow groundwater (phreatic) located from the center to the north of the lines to a depth of ± 13 m and deep groundwater, located varies in the middle of the lines from a depth of ± 15 m to the end with groundwater conditions may still be brackish due to the influence of seawater intrusion with a resistivity value of 0.1 Ohm.m identified to a depth of ± 25 m